Proses Sosialisasi dan Pembelajaran Moral dalam Cerita 'Gbagba': Tinjauan Kritis melalui Teori Sosialisasi - Andi Nurul Annisa Yudha; Sawedi Muhammad; Rahmat Muhammad (Equilibrium: Jurnal Pendidikan, 2025)
Robtel Neajai Pailey was awarded the International Anticorruption Excelence Award for her book, Gbagba. The twin brothers are from the port city of Buchanan who will be on vacation to their family home in the capital Monrovia. In this story socialization takes place through their interactions with relatives and the new environment in Monrovia. Sunday Ma and Sunday Ga face direct examples in everyday life, the injustices they witness and actions that do not match the values that their oracles teach. Robtel Neajai Pailey's "Gbagba" story provides an in-depth overview of the process of socialization and moral learning in children through their experiences in everyday life. This analysis uses the socialist theory approach ofasu to review how social values such as honesty, responsibility, and discipline are transmitted to the two main characters, Sunday Ma and Sunday Ga. Socialization is a fundamental process in the formation of character, personality, and moral cultivation of children. From bribes to traffic police to relationships or friendships that make people free from the law. This story is close to everyday life so it is easy to understand. Through the method of literature study, analysis is done through the theory of socialization how the process of socialization in Gbagba stories is described and can Gbagba become a story that can support the moral development of children through the portrayal of the process of interaction of the surrounding environment. The results of the review showed that moral learning in children was strongly influenced by the socialization they experienced in their families, schools, communities, and their interactions with other social institutions